Study on Stability Control Measures for Large Deformation of Carbonaceous Slate at Diversion Tunnel of Guzeng Hydropower Station - GUO Yi; CHEN Yang; JIANG Yufei; YIN Ziwen; HU Tianming; ZHANG Jixun (Renmin Zhujiang, 2020)
Carbonaceous slate has the characteristics of weak rock mass and softening by water.When hydraulic tunnel construction is carried out in this type of rock mass with high crustal stress,large deformation of surrounding rock will occur in most cases.The control of large deformation is the key and difficult point to ensure no delay on construction period and long-term stable operation of the project.Combined with the condition of large deformation of carbonaceous slate at diversion tunnel of the Guzeng Hydropower Station,based on the analysis of large deformation mechanism of carbonaceous slate,and according to the geological phenomena and possible hydrogeological problems revealed by the site construction,this paper analyzes the support system of the tunnel section by combining numerical analysis and on-site monitoring,and puts forward reasonable support suggestions for reference by similar projects.